Entscheidungsunterstützung zur Auswahl und Steuerung von Lieferanten und Lieferketten unter Berücksichtigung von Nachhaltigkeitsaspekten - Zimmer, Konrad (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2016)
In supplier management social and environmental aspects gain rising importance. The aim of this work is the development of a decision support system. For this purpose a two-stage approach is developed consisting of a risk model and a performance model. This approach enables decision makers both to improve the transparency along the supply chain and to evaluate the sustainability performance of suppliers efficiently.